Isopropyl 2-(5-iodo-3-methylsulfinyl-1-benzofuran-2-yl)acetate - Choi, Hong Dae (International Union of Crystallography, 2008)
In the title compound, C(14)H(15)IO(4)S, the O atom and the methyl group of the methylsulfinyl substituent lie on opposite sides of the plane of the benzofuran fragment. The crystal structure is stabilized by C—H⋯π interactions between a methyl H atom and the benzene ring of an adjacent molecule, and by weak intermolecular C—H⋯O hydrogen bonds.